Faktori povezani sa učestalošću ektopične trudnoće - Popovic, Miroslav D; Milić-Radić, Tanja (Scripta Medica, 2022)
Background/Aim: Ectopic pregnancy is defined as a pregnancy outside the uterine cavity, most often in the fallopian tube. It is a life-threatening condition and requires early diagnosis and adequate care. Aim of this study was to examine the frequency of ectopic pregnancy, as well as the influence of parity, age of patients and previous in vitro fertilisation (IVF) procedure on the occurrence of ectopic pregnancy.Methods: A retrospective research was conducted in the Clinic for Gynaecology and Obstetrics of the University Clinical Centre of the Republic of Srpska from 1st of January 2016 up to 31 of December 2018, which included 125 hospitalised patients with a confirmed diagnosis of ectopic pregnancy. Data on the age of patients, parity and previous IVF, as well as the method of treatment of patients with ectopic pregnancy were analysed and compared.Results: In the observed period, there were a total of 9781 births and in the same period, 125 patients with a diagnosis of ectopic pregnancy were hospitalised, which is 1.27 %. Pregnancy did not occur after IVF. Laparoscopy and drug therapy are represented almost equally, depending on the clinical picture and the wishes of the patients and open access was represented only sporadically.Conclusion: According to this research, the onset of ectopic pregnancy is not affected by age, parity and previous IVF, which does not fit into the results of world research. The most common form of treatment in our country is both laparoscopy and medical approach and open access occurs only sporadically, which fits into the recommendations of the relevant guides.
Keywords: Vanmaterična trudnoća; Paritet; Dob; Liječenje